The Role of the Surabaya City Manpower Service in Efforts to Resolve Industrial Relations Cases Through Mediation - Shohihah, Millatus; Ali Murtadho, Nazhif (LPPM Universitas Ekasakti Padang, 2024)
Industrial relations cases can give rise to conflicts between workers and employers which can be detrimental to the industry and society as a whole. In an effort to resolve industrial relations cases, the Surabaya City Manpower Office has an important role in facilitating mediation between the two parties. This research is a type of empirical juridical legal research using primary legal sources, namely obtained using direct interview techniques with the City Manpower Office, and referring to Law no. 2 of 2004 and Law no. 13 of 2003 as well as secondary legal sources obtained using library study techniques (library research) by collecting sources in the form of journal articles, books and related policy documents. The research results show that the Surabaya City Manpower Office has an important role in resolving industrial relations cases through mediation, such as gathering information, facilitating meetings between the two parties, providing suggestions and recommendations, and providing education to workers and entrepreneurs regarding their rights and obligations. However, the effectiveness of the Manpower Office's role still needs to be improved through increasing the competence of Manpower Office officers in conducting mediation, as well as strengthening coordination between the Manpower Office and various related parties in resolving industrial relations cases. This research provides an overview of the role of the Surabaya City Manpower Office in resolving industrial relations cases through mediation and can be a basis for developing further research in the future.